1995
DOI: 10.1182/blood.v86.7.2642.2642
|View full text |Cite
|
Sign up to set email alerts
|

Role of free protein S and C4b binding protein in regulating the coagulant response to Escherichia coli

Abstract: Previous studies showed that infusion of C4b-binding protein with sublethal Escherichia coli (E. coli) in the primate produced a consumptive coagulopathy followed by microvascular thrombosis and renal failure. The first objective of this study was to characterize the pathophysiology and mechanism of this phenomena following infusion of both these agents with emphasis on defining the role of free protein S. The second objective was to examine the relevance of this model to the hemolytic uremic syndrome. Infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Animal experiments of severe inflammation-induced coagulation activation convincingly show that compromising the protein C system results in increased morbidity and mortality, whereas restoring an adequate function of activated protein C (APC) improves survival and organ failure. 47 Interestingly, experiments in mice with a one-allele targeted deletion of the protein C gene (resulting in heterozygous protein C deficiency) have more severe DIC and organ dysfunction and a higher mortality than wild-type littermates. 48 A third inhibitory mechanism of thrombin generation involves TFPI, the main inhibitor of the tissue factor-factor VIIa complex.…”
Section: Prothrombotic Mechanisms In Sepsismentioning
confidence: 99%
“…Animal experiments of severe inflammation-induced coagulation activation convincingly show that compromising the protein C system results in increased morbidity and mortality, whereas restoring an adequate function of activated protein C (APC) improves survival and organ failure. 47 Interestingly, experiments in mice with a one-allele targeted deletion of the protein C gene (resulting in heterozygous protein C deficiency) have more severe DIC and organ dysfunction and a higher mortality than wild-type littermates. 48 A third inhibitory mechanism of thrombin generation involves TFPI, the main inhibitor of the tissue factor-factor VIIa complex.…”
Section: Prothrombotic Mechanisms In Sepsismentioning
confidence: 99%
“…Although it has been shown that the b-chain of C4bBP (which mainly governs the binding to protein S) is not very much affected during the acute-phase response, 38 support for this hypothesis comes from studies showing that the infusion of C4bBP in combination with a sublethal dose of Escherichia coli into baboons resulted in a lethal response with severe organ damage due to DIC. 39 Finally, but importantly, in sepsis the EPCR has been shown to be downregulated, which may further negatively affect the function of the protein C system. 40 Apart from these effects, sepsis may cause a resistance toward APC by other mechanisms, which are partly dependent on a sharp increase in factor VIII levels (released from endothelial cells) but partly occur by yet unidentified mechanisms.…”
Section: Regulation Of Thrombin Generationmentioning
confidence: 99%
“…Blockade of the activity of protein C by infusion of C4 binding protein turns a sublethal model of E. coli in baboons into a lethal model. 34 Blockade of EPCR by a neutralizing monoclonal antibody also increased mortality in the E. coli baboon model. 35 Vice versa, infusion of PC in the same model protected against DIC and dying.…”
Section: Tissue Factormentioning
confidence: 99%